Pengaruh Brand Trust dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Pengiriman Paket Pada PT. Jalur Nugraha Ekakurir (JNE) Semarang - Baskara, Garylda Chrisnatha; Rodhiyah, Rodhiyah; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research is motivated the development of freight forwarder in Indonesia are more advanced and encouraging service companies to further improve the quality of service. In particular, this study discusses the PT.JNE. PT.JNE sales from year to year fluctuations. If this condition is not addressed, then PT.JNE will not compete with other service companies in Indonesia.The purpose of research to determine the effect of brand trust and quality of service to the decision to use. Type of explanatory research, data collection through interviews with questionnaires, observation, and literature study. The sampling technique accidental sampling and purposive sampling. Sample of 100 people. Quantitative analysis techniques. Quantitative analysis using validity, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, cross tabulation, as well as the significance test (t test and F test).Results and discussion showed relatively good brand trust but are still classified as not good enough , brand trust has a considerable influence on the decision to use ( 12.9 percent ) and positive influence on the decision of the use of ( 0.255 ) . Classified service quality is not good enough but still quite good , service quality has a considerable influence on the decision of the use of ( 22 percent ) and a positive influence on the decision of the use of ( 0.267 ) . While the decision to use quite enough , but still quite a lot to be in the category of rare and often . Brand trust and service quality has a strong influence on the decision of the use of ( 26.2 percent ) .Â In conclusion Brand Trust significantly positive effect on the decision to use. Quality of service is significantly positive effect on the decision to use. Brand Trust and Quality of care significantly positive effect on the decision to use. Suggested PT. JNE should immediately conduct an increase in the intensity of promotion and advertising are more massive, renovate facilities and completeness of facilities and infrastructure, and improving managerial ability of employees to increase brand trust and quality of service that the company JNE can continue to survive in the midst of intense competition it is today.